PENGARUH PIJAT LAKTASI TERHADAP VOLUME ASI PADA PASIEN POST SECTIO CAESAREA PARITAS KE-1 DI RSUD BANDUNG KIWARI TAHUN 2024 - Aminuddin, Sri Hennyati; Sadiah, Yayah; Nurlatifah, Teni; Kartika, Ira (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
Insufficient breast milk (ASI) is the main reason why mothers stop giving breast milk (ASI), because mothers feel they cannot meet their baby's nutritional needs and there is no increase in the baby's weight. During this crisis, women who give birth by caesarean section often face problems providing breast milk (ASI). Based on data from the health profile of West Java province in 2020, the percentage of babies < 6 months who received exclusive breast milk (ASI) reached (56.5%). Failure to express breast milk (ASI) in mothers after giving birth can be caused by a lack of stimulation of the hormone oxytocin which plays an important role in the production of breast milk (ASI). This study aims to determine the effect of lactation massage on the volume of breast milk (ASI) in 1st parity post sectio caesarea (SC) patients at the Bandung Kiwari Regional Hospital. The type of research used was experimental (quasi experimental) with a Pretest-Posttest Control Group Design. This sampling technique is purpose sampling. The sample was taken with a total of 36 participants divided into 2 interventions, 18 people, 18 people in the control group were processed using statistical tests, namely the Independent Sample T-test. The cross tabulation results of the average respondent in the intervention group were 10.39 ml and the average value in the control group was 5.78 ml with the difference between the two being 4.61 ml. The results of the bivariate analysis test showed that there was a significant influence between the effects of lactation massage on first parity post partum cesarean section mothers on breast milk volume with a p-value of 0.000 < 0.05.